The Effect of Dietary Phytase Supplementation on Digestibility and Growth of Asian Seabass Lates calcarifer - Totok Yudhiyanto; Suminto Suminto; Diana Rachmawati (Fisheries and Marine Science Faculty - Jenderal Soedirman University, 2017)
The purpose of this research is to evaluate Asian sea bass digestibility and growth fed with phytase dietary supplementation on soybean based fish diet. The initial weight of fish was 4.99±0.2 g with stocking density of 20 fishes per tanks reared in 80 L tank of sea water for 6 weeks. Completely Randomized Design of 50% soybean meal with phytase supplementation of 0; 500; 1,000; and 1,500 FTU kg-1 and three replication was used in this trial. Chromium oxide (Cr2O3) was used as digestibility indicator. Multivariate anova and One way anova (SPSS); linear regression (Microsoft Excel) and polynomial orthogonal (Microsoft Excel and Maple) was used to analyze the data. The results of Multivariate anova showed that phytase supplementation affect total digestibility (KCT) and relative growth rate (RGR) of asian seabass significantly (P<0.01) with phytase dose 1,000 FTU. One way anova also indicated that phytase 1,000 FTU significantly affect all parameters. Apparent digestibility coefficient (ADC) phosphorus had a very significant and dominant effect to total digestibility with R2 = 0.9669 than ADC protein and ADC fat (linear regression). KCT significantly affects efficiency of dietary protein (EPP) 30.57% and protein efficiency ratio (PER) 0.67%. EPP and PER significantly effect RGR 1.56% day-1, simultaneously. The optimal dose of phytase supplementation is 1,220 FTU.